Sustainable Competitive Advantage: A Bibliometric Systematic Literature Review of Strategic Enablers and Future Research - Abimanyu Hendi Asyono; Palupi Lindiasari Samputra; Hary Djatmiko (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Sustainable Competitive Advantage (SCA) remains a fundamental concept in strategic management; however, existing studies are fragmented across multiple theoretical perspectives, limiting a comprehensive understanding of its conceptual evolution and future research directions. This study aims to examine the development of SCA research, define the concept structure of SCA, and propose evidence-based recommendations for future research. A systematic literature review (SLR) in combination with bibliometric analysis was carried out according to the PRISMA methodology. From the initial set of 3,970 records indexed in Scopus, 303 papers were selected for analysis, published in journals from 2015 to 2025. Descriptive statistics and co-occurrence keyword analysis were performed via VOSviewer. The results confirm a significant increase in the number of SCA research over the last decade and show the existence of three main thematic clusters: Strategic Resources and Capabilities, Innovation and Digital Transformation, and Sustainability and Market Orientation. The results prove a conceptual shift from traditional resource-based theories towards integrative models that combine organizational capabilities, digital transformation, and sustainability aspects. In addition, three promising areas for future research were identified: development of integrative models of strategic enablers, long-run impact of digital transformation on competitiveness, and comprehensive measurement and implementation of SCA. These findings contribute to strategic management literature by providing a systematic synthesis of the intellectual landscape and offering a robust agenda for future theoretical and empirical research.